CONTINUING A VEHICLE FITTED WITH RUN FLAT TYRES - Grzegorz MOTRYCZ; Karolina J. HELNARSKA; Piotr STRYJEK (Scientific Journal of Silesian University of Technology. Series Transport, 2021)
Modern vehicles are equipped with many systems that monitor the security of driving. An example is the tyre pressure monitoring system that shows a fault if the tyre pressure is lowered. Low tyre pressure or no pressure at all (0 kPa) means that continuing driving may lead to a dangerous situation. Prolonged driving of the vehicle at 0 kPa in the tyre ends with tyre burst, rim damage, or even loss of stability. Therefore, on the automotive market, manufacturers offer Run Flat tyres adapted to emergency driving with a pressure of 0 kPa. This article presents the results of an experimental research in the field of vehicle dynamics, continuing driving a vehicle with a loss of tyre pressure. These tests were carried out not only to confirm the data provided by tyre manufacturers and to verify the vehicle's driveability but also to analyse the effectiveness of stopping vehicles equipped with this type of tyres using, for example, police studs, especially when vehicles are used for crimes or terrorist activities.